Beyond National Religiosity: The Pericope of 1 Kings 3:3-14 and Leadership Challenges in Nigeria - Uroko, Favour (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Literature on leadership in Nigeria from the perspective of 1 Kings 3 is hard to find. In the pericope, Solomon was the successor to David in leadership. Solomon kept to the promises and good plans of his predecessor. The pericope shows the roles of godfathers in political leadership. This narrative is of great importance to Nigeria’s leadership challenges in the political arena. This article examines 1 Kings 3:3-14 and its relevance to the leadership challenges in Nigeria. Nigeria is a country where leaders blackmail their predecessors and surround themselves with sycophants and godfathers. Over the years literature has focused on Nigeria’s leadership challenges from the political, sociological and psychological angles. This study provides a theological response to Nigeria’s leadership challenges.